2017
DOI: 10.1108/hff-03-2016-0125
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-nanofluid flow with heat transfer past a stretching surface for the new heat flux model using numerical approach

Abstract: Sheet processing of magnetic nanomaterials is emerging as a new branch of smart materials manufacturing. The efficient production of such materials combines many physical phenomena including magnetohydrodynamics (MHD), nanoscale, thermal and mass diffusion effects. To improve understanding of complex inter-disciplinary transport phenomena in such systems, mathematical models provide a robust approach. Motivated by this, herein we develop a mathematical model for steady, laminar, magnetohydrodynamic, incompress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Malik et al [33] analyzed the MHD flow of Casson fluid and also found that the temperature decreased using the Cattaneo Christov heat flux model. Very recently, a similar study conducted for nanofluids [24,34] and diverse non-Newtonian fluid models such as Oldroyd B-fluid [35], Eyring Powell [36,37], Carreau fluid [38], viscoelastic fluid [39,40] and second grade fluid [41,42] resulted in the non-Fourier model leading to the reduction of the temperature distribution. Mahmood et al [43] designed the boundary layer flow of Casson nanofluid using Cattaneo-Christov heat flux model while Jamshed and Aziz [44] utilized the Casson hybrid TiO 2 -CuO/EG nanofluid on the stretched flow problem with entropy generation.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Malik et al [33] analyzed the MHD flow of Casson fluid and also found that the temperature decreased using the Cattaneo Christov heat flux model. Very recently, a similar study conducted for nanofluids [24,34] and diverse non-Newtonian fluid models such as Oldroyd B-fluid [35], Eyring Powell [36,37], Carreau fluid [38], viscoelastic fluid [39,40] and second grade fluid [41,42] resulted in the non-Fourier model leading to the reduction of the temperature distribution. Mahmood et al [43] designed the boundary layer flow of Casson nanofluid using Cattaneo-Christov heat flux model while Jamshed and Aziz [44] utilized the Casson hybrid TiO 2 -CuO/EG nanofluid on the stretched flow problem with entropy generation.…”
Section: Introductionmentioning
confidence: 94%
“…and eliminating q from Equations (1) and (4) will give a non-Fourier energy equation (see Akbar et al [24], Salahuddin et al [31], Kumar and Varma [34] and Khan et al [41])…”
Section: Cattaneo Christov Heat Flux Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cattaneo‐Christov model defines the heat flux, q , according to: q+γtrue[qt+VqqV+true(Vtrue)qtrue]=kTtrue¯.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…Ai and Li used a discontinuous Galerkin finite element method to simulate ultra‐short pulsed laser thermal processing of thin films with a non‐Fourier heat conduction model, observing significant boundary thermal wave reflection/interactions. Akbar et al used fourth order Runge‐Kutta shooting quadrature to compute the hydromagnetic flow of nanofluids from a stretching surface with the Cattaneo‐Christov heat flux model noting that heat transfer rates are substantially altered with non‐Fourier thermal relaxation effects. Further studies include Bhatti et al who simulated the multimode non‐Fourier heat transfer in electrically conducting viscoelastic boundary layer flow from an extending sheet noting that increasing thermal relaxation decreases the thermal layer boundary layer thickness.…”
Section: Introductionmentioning
confidence: 99%